The impact of corporate social responsibility strategy on the management and governance axis for sustainable growth - López, Belén; Rangel Pérez, Celia; Fernández, Manuel (Elsevier Inc., 2022)
The aim of this work is to show whether a continuous strategy in Corporate Social Responsibility (CSR) over time brings efficiency and profitability to the company's operations. The methodology used in this paper is based on two sets of variables: the scoring for 27 listed companies present in the Spanish MERCO Corporate Responsibility and Governance Ranking (MERCO CR&G Ranking),and their share price in the Spanish open stock market for said companies from 2011 to 2019. These variables are compared with regressive,autoregressive and moving average econometrical methods over time. Results reveal that: (i) there is a directly proportional relationship between CSR,measured by the MERCO CR&G Ranking,and the share price; (ii) such relationship loses relevance when considering the economic context; (iii) the great progress of CSR in terms of management,transparency,measurement,environment and governance translates into a crucial contribution to the efficiency and sustainable growth of the company. © 2022 The Authors
Keywords: Corporate social responsibility; Efficiency; Governance; Management; Sustainable growth; 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 9 - Industria, innovación e infraestructura